FACTORS INFLUENCING WOMEN'S PARTICIPATION IN RICE PROCESSING UNDER THE IFAD VALUE CHAIN DEVELOPMENT PROGRAMME (VCDP) IN NASARAWA STATE, NIGERIA - Yusuf, A.T.; Adejoh, S.O.; Anamayi, E.S.; Moses, O.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluates the socio-economic characteristics factors influencing women’s participation in rice processing activities under the International Fund for Agricultural Development (IFAD) Value Chain Development Programme (VCDP) in Nasarawa State, Nigeria. The specific objectives were to describe the socio-economic characteristics of rice processors participating in the IFAD-VCDP, evaluate the extent of women's participation in rice processing activities under the IFAD-VCDP and determine the factors influencing women's participation in rice processing activities under the IFAD-VCDP. A multi-stage sampling technique was employed to select 120 women rice processors. Data were collected through structured questionnaires and analyzed using descriptive statistics, Likert scale, and Ordered Probit regression model. Results show that the age mean average is 36years, key determinants of participation include household size (0.200, p < 0.01), years of education (0.100, p < 0.01), access to training (0.300, p < 0.01), income (0.250, p > 0.05), processing experience (0.150, p < 0.01), extension contacts (0.200, p < 0.05), credit access (0.250, p < 0.01), and cooperative membership (0.300, p < 0.05. This study has identified and analyzed the various factors influencing women's participation in rice processing activities under the IFAD Value Chain Development Programme (VCDP) in Nasarawa State, Nigeria. It was found that while the VCDP has positively impacted the agricultural value chain, women's participation in rice processing is still limited by several socio-economic, cultural, and structural barriers. Policy recommendations were made to enhance women's involvement in rice processing activities, which could contribute to rural economic development and food security.